Foresail-2: Space Physics Mission in a Challenging Environment - Anger Marius; Niemelä Petri; Cheremetiev Kiril; Clayhills Bruce; Fetzer Anton; Lundén Ville; Hiltunen Markus; Kärkkäinen Tomi; Mayank M.; Turc Lucile; Osmane Adnane; Palmroth Minna; et al. (Springer, 2025)
Earth’s radiation belts are extremely important for space weather because they can store and accelerate particles to relativistic energies, which can have a potential impact on satellite functionality, communications, and navigation systems. The FORESAIL consortium wants to measure these high-energy particle fluxes to understand the dynamics of the radiation belts with its satellite mission Foresail-2. The mission aims to measure magnetic ultra low frequency waves and the plasma environment in the magnetosphere around Earth. The captured data will help to improve our understanding of space weather, and in particular the dynamics of Earth’s radiation belts during periods of large disturbances inside the magnetosphere. A mission design analysis and several trade-off studies are conducted to find the requirements for the science payloads and spacecraft avionics design. Deducted from these requirements, four different payloads are proposed to gather science data in a highly elliptical orbit such as a geostationary transfer orbit. The precision magnetometer uses flux-gate technology to measure magnetic waves from 1 mHz to 10 Hz. The spin scanning particle telescope is built around a detector stack to measure electron spectra in the range of 30 keV to 10 MeV. Additionally, this mission serves as a technology demonstrator for the Coulomb drag experiment which proposes a new kind of electric solar wind sail utilising the Coulomb drag force imposed onto a 300 m long tether. The fourth payload investigates multilayer radiation shielding and single event effects. All payloads will be supported by a newly developed 6U platform using mostly commercial off-the-shelf components. Its proposed avionics face several unique design requirements rising from the payloads and the preferred highly elliptical orbit for this mission.